Needle in a Haystack – searching for your new faculty colleague - Jeff Bright (Academic Chairpersons Conference Proceedings, 2023)
The presenter and participants will explore best practices for conducting a search for a new faculty member. Topics covered in the session will include selecting search committee members, recruiting a candidate pool, virtual interviews, scheduling the campus visit, do’s, don’ts, and bias in the screening process.
Keywords: faculty; search; recruitment; bias; interview